Variació foneticofonològica. Una aproximació a la diversitat del vocalisme en lleidatà - Julià i Muné, Joan (Caplletra. Revista Internacional de Filologia, 1998)
This paper presents phonetic-phonological variation in articulatory and perceptual terms, both at segmental and suprasegmental levels. It also presents the determining factors of linguistic diversity and change, that is, the factors responsible for the external, geographical (intra-dialectal and inter-dialectal), chronolectal, social and functional variation of a language. Several examples of a few relevant phenomena of the Northwestern phonetics in Lleida are included, especially the phenomenon of vocalism as seen from the relation between internal and external variation of a language.